Hyperkyphosis, Kyphosis Progression, and Risk of Non-Spine Fractures in Older Community Dwelling Women: The Study of Osteoporotic Fractures (SOF) - Kado, Deborah M. (2014)
While accentuated kyphosis is associated with osteoporosis, it is unknown whether it increases risk of future fractures, independent of bone mineral density (BMD) and vertebral fractures. We examined the associations of baseline Cobb angle kyphosis and 15 year change in kyphosis with incident non-spine fractures using data from the Study of Osteoporotic Fractures. A total of 994 predominantly white women, aged 65 or older, were randomly sampled from 9,704 original participants to have repeated Cobb angle measurements of kyphosis measured from lateral spine radiographs at baseline and an average of 15 years later. Non-spine fractures, confirmed by radiographic report, were assessed every four months for up to 21.3 years. Compared with women in the lower three quartiles of kyphosis, women with kyphosis greater than 53 degrees (top quartile) had a 50% increased risk of non-spine fracture (95% CI, 1.10 –2.06 after adjusting for BMD, prevalent vertebral fractures, prior history of fractures, and other fracture risk factors. Cobb angle kyphosis progressed an average of 7 degrees (SD = 6.8) over 15 years. Per 1 SD increase in kyphosis change, there was a multivariable adjusted 28% increased risk of fracture (95% CI, 1.06 – 1.55) that was attenuated by further adjustment for baseline BMD (HR per SD increase in kyphosis change, 1.19; 95% CI 0.99 –1.44). Greater kyphosis is associated with an elevated non-spine fracture risk independent of traditional fracture risk factors in older women. Furthermore, worsening kyphosis is also associated with increased fracture risk that is partially mediated by low baseline BMD that itself is a risk factor for kyphosis progression. These results suggest that randomized controlled fracture intervention trials should consider implementing kyphosis measures to: 1) further study kyphosis and kyphosis change as an additional fracture risk factor; and 2) test whether therapies may improve or delay its progression.